Sahih Al Bukhari: being the traditions of saying and doings of the prophet Muhammad AS narrated by his companions to those who followedthem/ and compiled under the title kitab al jami' as sahih - Abi Abdullah Muhammad bin Ismail Al Bukhari (Kitab Bhavan, 1978)
ws.jl.5.c.1-2